A meta-analysis of the comparing of the first-generation and next-generation TKIs in the treatment of NSCLC - Yongxing Li; Jianye Yang; Yufen Xu; Ming Zhang; Xiaoping Zhang; Wenyu Chen; Xiaodong Lv (Mathematical Biosciences and Engineering, 2019)
BackgroundThe current standard approach to the treatment of patients with non-small-cell lung cancer (NSCLC) harboring epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI)—sensitizing mutations has been the treatment with a first-generation EGFR-TKIs. While, with resistance developed against first-generation EGFR-TKIs, second/third-generation TKIs have attracted all the attention, and replaced first-generation EGFR- TKIs upon disease progression due to the greater efficacy and more favorable tolerability. In the past few years, this strategy has been challenged by clinical evidence when next-generation EGFR-TKIs are used in patients with advanced NSCLC. ObjectiveIn this study, we performed a meta- analysis to investigate the efficacy of next-generation TKIs comparison with first-generation TKIs in the treatment of NSCLC. MethodsThe multiple databases including Pubmed, Embase, Cochrane library databases were adopted to search for the relevant studies, and full-text articles involving to comparison of next-generation TKIs and first-generation TKIs were reviewed. After rigorous reviewing on quality, the data was extracted from eligible randomized controlled trial (RCT). Meta-analysis Revman 5.3 software was used to analyze the combined pooled ORs with the corresponding 95% confidence interval using fixed- or random-effects models according to the heterogeneity. ResultsA total of 5 randomized controlled trials were included in this analysis. The group of next-generation TKIs did achieved benefit in progression-free survival (PFS) (OR = 0.58, 95%CI = 0.45-0.75, P < 0.0001), overall survival (OS) (OR = 0.76, 95%CI = 0.65-0.90, P = 0.001) as well with the objective response rate (ORR) (OR = 1.27, 95%CI = 1.01-1.61, P = 0.04), respectively. In the results of subgroup analysis of PFS with EGFR mutations, there is also significant differences with exon 19 deletion (OR = 0.56, 95%CI = 0.41-0.77, P = 0.0003) and exon 21 (L858R) mutation (OR = 0.60, 95%CI = 0.49-0.75, P < ＝0.00001). While, the treatment-related severe adverse event (SAE) between the next-generation TKIs and first-generation TKIs did not have statistical significance (OR = 1.48, 95%CI = 0.62-3.55, P = 0.38). ConclusionThe next-generation TKIs significantly improved efficacy outcomes in the treatment of EGFR mutation-positive advanced NSCLC compared with the first-generation TKIs, with a manageable safety profile. These results are potentially important for clinical decision making for these patients.